2007
DOI: 10.1016/j.brainresrev.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Permanent, bilateral common carotid artery occlusion in the rat: A model for chronic cerebral hypoperfusion-related neurodegenerative diseases

Abstract: Chronic cerebral hypoperfusion has been associated with cognitive decline in aging and Alzheimer's disease. Moreover, the pattern of cerebral blood flow in mild cognitive impairment has emerged as a predictive marker for the progression into Alzheimer's disease. The reconstruction of a pathological condition in animal models is a suitable approach to the unraveling of causal relationships. For this reason, permanent, bilateral occlusion of the common carotid arteries (2VO) in rats has been established as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
546
3
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(595 citation statements)
references
References 104 publications
(168 reference statements)
31
546
3
15
Order By: Relevance
“…133 A number of anti-inflammatory agents and free radical scavenging agents have shown benefit. 114 Treatments with minocycline significantly attenuated the hypoxia-ischemia-induced brain injury and improved neurobehavioral performance; the protection of minocycline was associated with its ability to reduce microglial activation. 134 In the SHR/SP with the Japanese permissive diet and unilateral carotid artery occlusion, treatment with minocycline blocked the full development of white-matter injuries seen on MRI and improved behavior in the Morris water maze.…”
Section: Treatments In Animal Modelsmentioning
confidence: 91%
See 1 more Smart Citation
“…133 A number of anti-inflammatory agents and free radical scavenging agents have shown benefit. 114 Treatments with minocycline significantly attenuated the hypoxia-ischemia-induced brain injury and improved neurobehavioral performance; the protection of minocycline was associated with its ability to reduce microglial activation. 134 In the SHR/SP with the Japanese permissive diet and unilateral carotid artery occlusion, treatment with minocycline blocked the full development of white-matter injuries seen on MRI and improved behavior in the Morris water maze.…”
Section: Treatments In Animal Modelsmentioning
confidence: 91%
“…Treatments in rats with hypoxic hypoperfusion due to either BCAO or spontaneous hypertension have indicated a number of potential therapeutic agents. 114,131 Cyclosporin A suppressed both glial activation and white-matter changes after chronic cerebral hypoperfusion, suggesting that immunologic reaction may have a role in the pathogenesis of the whitematter changes. 132 Cyclosporine A inhibits BBB breakdown in APOE4 Tg mice by inihibiting cyclophilin A-MMP-9 pathway in pericytes leading to reversal of neuronal dysfunction and secondary neurodegenerative changes.…”
Section: Treatments In Animal Modelsmentioning
confidence: 99%
“…Bilateral common carotid artery occlusion (two-vessel occlusion, 2VO) was carried out in rats (Sarti et al 2002a(Sarti et al , 2002bFarkas et al 2007) according to the scheme represented in Fig. 1A, according to the method previously published (Lana et al 2014).…”
Section: Surgerymentioning
confidence: 99%
“…The permanent, bilateral occlusion of the common carotid arteries of rats (two-vessel occlusion, 2VO) is a procedure that mimics age-related cerebrovascular stenosis and is widely utilized to investigate the mechanisms of chronic cerebral hypoperfusion and consequent neurodegenerative processes (Farkas et al 2007;Sarti et al 2002aSarti et al , 2002bLana et al 2014). The 2VO model has revealed that, the CA1 region of the hippocampus is particularly vulnerable not only to acute ischemia but also to hypoperfusion given by the 2VO, with consequent failure of neuronal signaling, and to learning and memory disturbances (Farkas et al 2006;Melani et al 2010;Ohtaki et al 2006;Schmidt-Kastner et al 2001;Shibata et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4 Bilateral common carotid artery occlusion has been widely used in the rat to model chronic cerebral hypoperfusion. 5 Recently, mouse bilateral common carotid artery stenosis (BCAS) models have emerged. 6 In these models, although the degree of hypoperfusion is correlated with the extent of ischemic lesions and neurologic impairment, 7 the magnitude of flow reductions after BCAS were moderate at best (~30 to 40%), 8 at least relative to classic ischemic thresholds of 80 to 85%, [9][10][11] and lasted only a few days before collateral development and recovery of flow.…”
Section: Introductionmentioning
confidence: 99%